PERTUMBUHAN DAN PERKEMBANGAN MIKROORGANISME TANAH PADA MEDIA AGAR EKSTRAK TANAH YANG DIPENGARUHI HERBISIDA GLYFOSAT - Agustian Agustian; Ari Prima Wahyudi; Oktanis Emalinda (Jurnal Solum, 2005)
Soil microorganisms have significant role in plant nutrient cycles availability. Repeated glyphosate application and unwise use this herbicide may give an impact in soil microorganism population and create a shift in community structure in soil microcosm. The objectives of this study were to (1) analyze the effects of different glyphosate application rates on soil mcroorganism population and community structure. The research have done in two series i.e. in limed soil extract and unlimed soil extract media. Five treatments and 3 replications arranged in Completely Randomized Design were used in this experiment. The treatments assay were doses of glyphosat application i.e : without glyphosat, 2 ml, 4 ml, 6 ml and 8 ml of glyphosate. Duncans New Multiple Range Test were used to compare the results obtained in this experiment. Total population obtained in 2 ml application of glyphosate in soil extract agar medium are 5.6x108 g-1 of soil or decreasing 50%. If doses of glyphosate increase to 8 ml the total of population diminished 75%. The glyphosate application have only influence to fungi population but not to the total population in limed soil extract agar. The diameter of bacteria and fungi colony observed in unlimed or limed soil extract agar media decrease by rising of doses glyphosate application and have the same as the population pattern. Key words : Glyphosate, soil microorganism, Ultisol